2014
DOI: 10.1128/jvi.02617-13
|View full text |Cite
|
Sign up to set email alerts
|

Malsoor Virus, a Novel Bat Phlebovirus, Is Closely Related to Severe Fever with Thrombocytopenia Syndrome Virus and Heartland Virus

Abstract: During a survey in the year 2010, a novel phlebovirus was isolated from the Rousettus leschenaultii species of bats in western India. The virus was identified by electron microscopy from infected Vero E6 cells. Phylogenic analysis of the complete genome showed its close relation to severe fever with thrombocytopenia syndrome (SFTS) and Heartland viruses, which makes it imperative to further study its natural ecology and potential as a novel emerging zoonotic virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 26 publications
1
56
0
2
Order By: Relevance
“…However, it is also possible that at least some of these results are attributable to circulation of a different, unidentified, phlebovirus. Mourya et al [30] reported a novel bat phlebovirus named Malsoor virus, related to severe fever with thrombocytopenia syndrome virus (SFTSV). Malsoor virus was isolated from a related fruit bat ( Rousettus leschenaultia ) in Western India [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is also possible that at least some of these results are attributable to circulation of a different, unidentified, phlebovirus. Mourya et al [30] reported a novel bat phlebovirus named Malsoor virus, related to severe fever with thrombocytopenia syndrome virus (SFTSV). Malsoor virus was isolated from a related fruit bat ( Rousettus leschenaultia ) in Western India [30].…”
Section: Discussionmentioning
confidence: 99%
“…Mourya et al [30] reported a novel bat phlebovirus named Malsoor virus, related to severe fever with thrombocytopenia syndrome virus (SFTSV). Malsoor virus was isolated from a related fruit bat ( Rousettus leschenaultia ) in Western India [30]. Mossel et al [21] reported two isolations of Arumowot virus ( Phenuiviridae, Phlebovirus ) from Culex mosquitoes collected in Jinja, Uganda, in 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis showed highest homology with known sequences of Phleboviruses and was found to be distinctly close to Heartland and severe fever with thromocytopenia syndrome (SFTS) viruses12.…”
Section: Resultsmentioning
confidence: 84%
“…In the latter case, the virus-termed SFTSV strain YG1-was isolated from a patient who died from a febrile illness of unknown etiology, although since the patient had never travelled abroad, she is thought to have been infected in Japan (24). Notably, two cases of a similar febrile illness with thrombocytopenia have been reported in Missouri, USA, and the causative agent, named Heartland virus, was determined to be a novel tick-borne phlebovirus closely related to SFTSV (18,19). SFTSV belongs to the genus Phlebovirus of the family Bunyaviridae (27,29).…”
mentioning
confidence: 99%